Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\sqrt{3+2\sqrt{2}}-\dfrac{1}{2}\sqrt{8}\)
\(=\sqrt{2}+1-\sqrt{2}\)
=1
a: Hàm số này đồng biến vì \(2-\sqrt{3}>0\)
b: \(f\left(2+\sqrt{3}\right)=4-3-1=0\)
\(f\left(\sqrt{3}\right)=2\sqrt{3}-3-1=2\sqrt{3}-4\)
\(A=1+\frac{2}{\sqrt{x}+1};B=\frac{\sqrt{x}}{\sqrt{x}-1}+\frac{1}{\sqrt{x}+2}-\frac{3\sqrt{x}}{x+\sqrt{x}-2}\)
đề bài là thế này ạ!?
Bài 1:
a) \(B=\sqrt{1-4x+4x^2}\)
\(=\sqrt{\left(1-2x\right)^2}\)
\(=\left|1-2x\right|\)
Nếu \(x\le\frac{1}{2}\)thì: \(B=1-2x\)
Nếu \(x>\frac{1}{2}\)thì: \(B=2x-1\)
b) Tại \(x=-7\)thì: \(B=1-2.\left(-7\right)=15\)
a) Ta có: \(\dfrac{2}{\sqrt{3}-1}+\dfrac{3}{\sqrt{3}-2}+\dfrac{12}{3-\sqrt{3}}\)
\(=\dfrac{2\left(\sqrt{3}+1\right)}{2}-\dfrac{3\left(2+\sqrt{3}\right)}{1}+\dfrac{12\left(3+\sqrt{3}\right)}{6}\)
\(=\sqrt{3}+1-6-3\sqrt{3}+2\left(3+\sqrt{3}\right)\)
\(=-2\sqrt{3}-5+6+2\sqrt{3}\)
=1
b) Ta có: \(\dfrac{1}{\sqrt{3}-\sqrt{2}}-\dfrac{2}{\sqrt{7}+\sqrt{5}}-\dfrac{3}{\sqrt{5}-\sqrt{2}}+\dfrac{4}{\sqrt{7}+\sqrt{3}}\)
\(=\sqrt{3}+\sqrt{2}-\sqrt{7}+\sqrt{5}-\sqrt{5}-\sqrt{3}+\sqrt{7}-\sqrt{3}\)
\(=\sqrt{2}-\sqrt{3}\)
a: Ta có: \(4\sqrt{3a}-3\sqrt{12a}+\dfrac{6\sqrt{a}}{3}-2\sqrt{20a}\)
\(=4\sqrt{3a}-6\sqrt{3a}+2\sqrt{2a}-4\sqrt{5a}\)
\(=-2\sqrt{3a}+2\sqrt{2a}-4\sqrt{5a}\)